Análise dos gols da liga paulista de futsal 2018 - Oliveira, Igor Jardim Morisugi de [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Futsal is a high intensity sport that can be maintained due to the unlimited number of substitutions. It is played in a small space of 40 x 20 m, with 5 players, I get one of them the goalkeeper. Due to the reduced space there is great incidence of goals. The characteristics of how goals in futsal happen are still not clear. Thus, the objective of this study was to classify the types of goals, to analyze the finishing and entry points of the ball in the goal and if there is a difference of occurrences between the first and second time, in the qualifying phase of the Paulista Futsal 2018 League. of the 17 teams in which 125 goals were scored. At least one game from each team was analyzed inside and outside the home. The games were analyzed through the VideoObserver and YouTube platforms. The division of the court was made through the half of the court, which was divided into six equal parts (from the bottom line to the 10m line) and the seventh is between the 10m and half court lines and the division of the goal was in six equal parts. The goals were classified into 14 categories and most of the goals were scored as counterattack (27%) and exchange of passes (21%) and the other rankings were equal to or less than 7% of total goals . In most of the goals the ball was finished (origin) of the central part of the court (60.00%), that was delimited with 10m of length ahead of the goal and with width of 20m. The lower sectors of the goal were where the ball most entered, with 76.80% of the goals. It is concluded that the result of 76,80% referring to goals that entered the lower sectors of the goal shows that players prefer to finish in this lower part because the goal is small and higher kicks could miss the target compared to kicks lower. With 60.00% of the completions made in the middle of the court... (Complete abstract electronic acess below)

O futsal é um esporte de alta intensidade, que pode ser mantida devido ao número ilimitado de substituições. Ele é jogado em um espaço reduzido de 40 x 20 m, com 5 jogadores, sedo um deles o goleiro. Devido ao espaço reduzido há grande incidência de gols. As características de como ocorrem os gols no futsal ainda não estão bem claras. Assim, o objetivo deste estudo foi classificar os tipos de gols, analisar os locais de finalização e entrada da bola na meta e se há diferença das ocorrências entre o primeiro e segundo tempo, na fase classificatória da Liga Paulista de Futsal 2018. Foram analisados 47 jogos das 17 equipes em que ocorreram 125 gols. Pelo menos um jogo de cada equipe foi analisado dentro e fora de casa. Os jogos foram analisados por meio da plataforma VideoObserver e YouTube. A divisão da quadra foi feita através da metade da quadra, que foi dividida em seis partes iguais (da linha de fundo até a linha dos 10m) e a sétima parte se encontra entre a linha dos 10m e a metade da quadra e a divisão da meta foi em seis partes iguais. Os gols foram classificados em 14 categorias, e a maioria dos gols foi classificada como contra-ataque (27%) e troca de passes (21%) e as demais classificações foram iguais ou inferiores a 7% do total de gols. Na maior parte dos gols a bola foi finalizada (origem) da parte central da quadra (60,00%), que foi delimitada com 10m de comprimento à frente da meta e com largura de 20m. Os setores inferiores da meta foram a onde a bola mais entrou, com 76,80% dos gols. Conclui-se que o resultado de 76,80% referente aos gols que entraram nos setores inferiores da meta, mostra que os jogadores preferem finalizar nesta parte mais baixa, pois a meta é pequena e chutes mais altos poderiam errar o alvo se comparados a chutes mais baixos. Com 60,00% das finalizações realizadas na parte central da quadra... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Futsal; Olheiros (futebol); Jogos de bola